Pengalaman Komunikasi dan Adopsi Teknologi Komunikasi dalam Menjalankan Organisasi Mahasiswa selama Pandemi Covid-19 - Kholidil Amin (Avant Garde, 2021)
The Covid-19 pandemic, which has lasted a long time, requires organizations to adapt in running their organizational work programs. BEM FISIP Universitas Brawijaya 2020 experienced it, which requires the members to be adaptive to the pandemic situation. Changes in organizations' work ways occur in implementing work programs, coordination, and bonding activities between members that must be carried out online. Adoption of communication technology is one of the solutions applied by the organizations. Some previous research has explained that a pandemic situation makes individuals have subjective communication experiences in response to a pandemic. Using an interpretive paradigm and phenomenology, the present research seeks to explain what organizational management experience in running their organizations during the Covid-19 pandemic. The present study also aims to explain what obstacles are experienced and how to overcome the organization's obstacles during the Covid-19 pandemic. The results revealed that the members experienced advantages and disadvantages in running the organization during the pandemic. The study found that the members experienced constraints; however, they have adaptive solutions to face the pandemic. Another finding is that there are different experiences in carrying out organizational activities by members who suppose they are introverts or extroverts.